C(alkenyl)–H Activation via a Six-Membered Palladacycle: Catalytic Synthesis of 1,3-Dienes - Liu, Mingyu (J Am Chem Soc, 2018)
A catalytic method to prepare highly substituted 1,3-dienes from two different alkenes is described using a directed, palladium(II)-mediated C(alkenyl)–H activation strategy. The transformation exhibits broad scope across three synthetically useful substrate classes masked with suitable bidentate auxiliaries (4-pentenoic acids, allylic alcohols, and bishomoallylic amines) and tolerates internal non-conjugated alkenes, which have traditionally been a challenging class of substrates in this type of chemistry. Catalytic turnover is enabled by either MnO(2) as the stoichiometric oxidant or by co-catalytic Co(OAc)(2) and O(2) (1 atm). Experimental and computational studies were performed to elucidate the preference for C(alkenyl)–H activation over other potential pathways. As part of this effort, a structurally unique alkenylpalladium(II) dimer was isolated and characterized.